2017
DOI: 10.1186/s12864-017-4152-1
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration induced transcriptomic responses in two Tibetan hulless barley (Hordeum vulgare var. nudum) accessions distinguished by drought tolerance

Abstract: BackgroundThe harsh environment on the Qinghai-Tibetan Plateau gives Tibetan hulless barley (Hordeum vulgare var. nudum) great ability to resist adversities such as drought, salinity, and low temperature, and makes it a good subject for the analysis of drought tolerance mechanism. To elucidate the specific gene networks and pathways that contribute to its drought tolerance, and for identifying new candidate genes for breeding purposes, we performed a transcriptomic analysis using two accessions of Tibetan hull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Unfortunately, to date, only limited progress has been made to enhance the stress tolerance in this crop. More importantly, several studies have focused on drought and cold tolerance enhancement in hulless barley (Deng et al 2013; Zeng et al 2016; Liang et al 2017; Xu et al 2017; Yuan et al 2017) but research on the salinity tolerance has been largely overlooked. The salinization of cropland soil in the Tibetan Plateau has become an increasingly serious concern for agricultural production (Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, to date, only limited progress has been made to enhance the stress tolerance in this crop. More importantly, several studies have focused on drought and cold tolerance enhancement in hulless barley (Deng et al 2013; Zeng et al 2016; Liang et al 2017; Xu et al 2017; Yuan et al 2017) but research on the salinity tolerance has been largely overlooked. The salinization of cropland soil in the Tibetan Plateau has become an increasingly serious concern for agricultural production (Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the tolerant accession XL significantly regulated a larger variety of metabolites than the sensitive accession, which may promote the establishment of a robust system to cope with the stress [29]. This result was expected given that Liang et al [12] also observed that their tolerant hulless barley genotype significantly regulated a higher number of genes than the sensitive one under drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Based on transcriptome analysis, 853 differentially expressed genes were detected as involved in drought response and categorized into nine clusters enriched in various biological pathways in a drought tolerant hulless barley genotype [11]. More recently, by comparing two genotypes with contrasting tolerance to drought, Liang et al [12] reported that the tolerant genotype has more upregulated genes than the sensitive one and found several exclusively enriched pathways in the tolerant genotype. Overall, these studies provided important insights into the molecular mechanisms of hulless barley tolerance to drought.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results reported here do indicate that genetic variation between the three genotypes has significant and measurable impacts on patterns of gene expression in response to water stress. The fact that such variation should exist is not surprising and there are numerous examples of gene-expression studies and QTL analyses for different aspects of drought tolerance in forage and other grasses (e.g., Alm et al, 2011 ; Merewitz et al, 2014 ; Baldoni et al, 2016 ; Jiang et al, 2017 ; Liang et al, 2017 ; Zhu et al, 2017 ; Cheruiyot et al, 2018 ; Hu et al, 2018 ; Ji et al, 2018 ; Kumar et al, 2018 ; Ling et al, 2018 ; Ma et al, 2018 ; Chaichi et al, 2019 ; Dinkins et al, 2019 ; Fradera-Sola et al, 2019 ). However, in the context of Brachiaria breeding, these genotypes were selected from a cultivar development program and the results suggest selectable variation with measurable impacts.…”
Section: Discussionmentioning
confidence: 99%